Economic Empowerment with Hydroponic Vegetable Cultivation as a Stunting Prevention Solution - Dewi; Zefri Maulana; Irfan Irfan Nasruddin (Fakultas Ekonomi dan Bisnis Islam Institut Agama Islam Negeri Langsa, 2024)
This research explores economic empowerment and hydroponic vegetable cultivation to prevent stunting in Matang Setui Village. Children showing signs of stunting in the village face a shortage of Supplementary Feeding Program (SFP) from the local health center team. Through collaboration between economic and innovative agricultural aspects, this study aims to improve the quality of life in the community and reduce the incidence of stunting in children. Hydroponics is chosen as an effective agricultural solution for producing quality vegetables without the limitations of traditional methods.The focus of this research is the implementation of economic empowerment programs, including skills training, entrepreneurial guidance, and increased access to economic resources. The introduction of hydroponic vegetable cultivation is also proposed as an innovative solution to enhance food security and nutritional standards in the community. With comprehensive data analysis and evaluation of empowerment impacts, this research aims to provide insights into the positive impact of economic collaboration and hydroponic vegetable cultivation in addressing stunting challenges.